2017
DOI: 10.1631/jzus.b1600303
|View full text |Cite
|
Sign up to set email alerts
|

Use of liposomal doxorubicin for adjuvant chemotherapy of breast cancer in clinical practice

Abstract: Breast cancer is one of the malignant tumors with the highest morbidity and mortality. It is helpful to reduce the rate of tumor recurrence and metastasis by treating breast cancer with adjuvant chemotherapy, so as to increase the cure rate or survival of patients. In recent years, liposomes have been regarded as a kind of new carrier for targeted drugs. Being effective for enhancing drug efficacy and reducing side effects, they have been widely used for developing anticancer drugs. As a kind of anthracycline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 53 publications
(52 reference statements)
0
52
0
1
Order By: Relevance
“…Two liposomal formulations have been approved for use with certain defined clinical indications. One liposomal DOX (Caelyx ® Janssen Pharmaceutica NV, Beerse (Belgium) in Europe and Doxil ® Janssen Products LP, Horsham (England) in the USA) has polyethylene glycol (PEG) embedded in the lipid layer; other formulations of DOX (Myocet ® ) GP‐Pharm, Barcelona (Spain) adopt uncoated liposomes …”
Section: Strategies For Preventionmentioning
confidence: 99%
“…Two liposomal formulations have been approved for use with certain defined clinical indications. One liposomal DOX (Caelyx ® Janssen Pharmaceutica NV, Beerse (Belgium) in Europe and Doxil ® Janssen Products LP, Horsham (England) in the USA) has polyethylene glycol (PEG) embedded in the lipid layer; other formulations of DOX (Myocet ® ) GP‐Pharm, Barcelona (Spain) adopt uncoated liposomes …”
Section: Strategies For Preventionmentioning
confidence: 99%
“…Typically, taxanes and anthracyclines are included in the chemotherapy treatment protocol. The most widely used drug for patients with breast cancer metastases is doxorubicin (sold under the trade names Adriamycin and Adriblastina, among others) .…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the mag.SLPs were capable of effective killing of human tumor cells, including their drug-resistant sublines, even without a conjugated anticancer drug. The anticancer effect of the mag.SLPs was comparable to that of doxorubicin (Dox), a cornerstone and gold standard in the anticancer chemotherapy (Lippens et al, 1998;Minotti et al, 2004;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 94%